INTERPERSONAL COMMUNICATION BETWEEN TEACHERS AND STUDENTS IN FACILITATING THE TEACHING AND LEARNING PROCESS - Suroso Suroso; Kurniah Astutik; Hudson Sidabutar (CV. ADIBA AISHA AMIRA, 2025)
Effective communication is a key element in creating a productive and conducive learning environment. This research uses the literature study method to analyze the impact of teachers' communication competence and classroom culture on the learning process. The study revealed several important findings. First, teachers' ability to deliver material clearly and listen to students actively can increase students' participation and engagement in the classroom. Second, respect for learners' socio-cultural backgrounds can prevent misunderstanding and create an inclusive learning atmosphere. Third, emotional support from teachers has been proven to increase students' motivation to learn and help minimize behavioral problems in the classroom. Therefore, teachers' communication competence needs to be continuously improved to maximize the learning process.